Lessons from the structural adjustment process in Jamaica. - ROBINSON, John W. (1994)
Examines the structure of the economy prior to adjustment, the pattern of output, income, the price and incentive systems, and the likely direction of indicators given the existing set of policies. Describes the structural adjustment measures, the institutional changes, and the external support which attended them. Assesses the degree of transformation which ensued and the extent to which the process has lived up to expectations.